Investigation of inverse emulsion assisted controlled release of polyacrylamides for enhanced oil recovery. Issue 21 (16th April 2019) - Liu, Zheyu; Mendiratta, Shruti; Chen, Xin; Zhang, Jian; Li, Yiqiang
Abstract : A high-molecular-weight polyacrylamide-based polymer encapsulated in water-in-oil emulsion is proposed for enhanced oil recovery. Its high viscosity, viscoelasticity and plugging capacity with aging time are beneficial for oil mobilization. Abstract : Conventional polymer flooding ( e.g. using polyacrylamide) has been widely used in the oil fields as an economical means for enhanced oil recovery. However, its efficacy is affected by the polymer properties and increasingly harsh reservoir conditions. In this study, a high-molecular-weight modified polyacrylamide polymer (GF-1 ) encapsulated in a water-in-oil emulsion is proposed for controlled polymer release towards enhanced oil recovery. It is compared with the conventional polyacrylamide in terms of their microscopic morphology, dissolving capacity, concentration–viscosity relationship, and rheological properties. It contained swollen polymer micelles and gradually released the polymer after phase inversion, which caused its viscosity, viscoelasticity, and plugging capacity to increase with aging time. The plugging analysis surprisingly showed a four-fold increase in the dimensionless breakthrough pressure of the emulsion polymer and five-fold increase in the residual resistance factor after five days of aging, confirming the significant increase in viscosity in confined spaces. The most interesting results were obtained by parallel core flooding experiments, where a higher recovery factor of 2.7% more than the conventional polymer was observed forGF-1 andGF-1 outperformed the conventional polymer by 6.9% in the low permeability zone. This emulsion polymer is a promising material to achieve enhanced oil recovery using in-depth profile modification in future oilfield related efforts.